PERANCANGAN VLAN ( VIRTUAL LOCAL AREA NETWORK ) UNTUK MANAJEMEN IP ADDRESS PADA POLITEKNIK SEKAYU - Ekkal Prasetyo (Politeknik Sekayu, 2014)
Rapidly development of network application needed high speed in the current information between application server and client or between servers with other server so that it was needed a good network infrastructure that could fill its necessity. In this research, the researcher will construct a computer network infrastructure design at Politeknik Sekayu, by using IP Address Management to improve network activities through Management and Security improvement by applying Virtual Local Area Network (VLAN) concept. The basic concept of VLAN was broadcast domain which was divided into some smaller segments according to the similarity of working unit and also the applications were used for each computer connected to network. This segmentation was done to restrict data packet distribution, so the data packet were delivered could be accepted by wanted users. In this study, the researcher also made configuration router for rescuing by using DHCP (Dynamic Host Configuration Protocol), and made an access limitation to the applications in the computer server according to VLAN groups have been determined before. By helping of network simulation software Cisco Packet Tracer 5.3 version, the researcher could make a simulation of proposed design before it was implemented directly. By it design, the researcher expects that users can access network without find disturbance of traffic and limited bandwidth which was caused by sending of data packet. And also it gave a guarantee of an application security in the server, because this application just can be accessed by host in the same VLAN group as the server.